Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00122-013-2065-1
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, genetic diversity and linkage disequilibrium in elite winter wheat assessed with SNP and SSR markers

Abstract: Modern genomics approaches rely on the availability of high-throughput and high-density genotyping platforms. A major breakthrough in wheat genotyping was the development of an SNP array. In this study, we used a diverse panel of 172 elite European winter wheat lines to evaluate the utility of the SNP array for genomic analyses in wheat germplasm derived from breeding programs. We investigated population structure and genetic relatedness and found that the results obtained with SNP and SSR markers differ. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
91
7
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 40 publications
31
91
7
3
Order By: Relevance
“…SSRs from genome and transcriptome sequences have been widely used for genetic diversity analysis and map construction (Emanuelli et al, 2013;Frascaroli et al, 2013;Würschum et al, 2013). In our study, the mean value of PIC (0.63) was less than that (0.67) previously reported for genomic-SSRs (Jiao et al, 2012), but significantly higher than the figure (0.44) for EST-SSRs (Zhang et al, 2012).…”
Section: Ssr Polymorphismcontrasting
confidence: 76%
“…SSRs from genome and transcriptome sequences have been widely used for genetic diversity analysis and map construction (Emanuelli et al, 2013;Frascaroli et al, 2013;Würschum et al, 2013). In our study, the mean value of PIC (0.63) was less than that (0.67) previously reported for genomic-SSRs (Jiao et al, 2012), but significantly higher than the figure (0.44) for EST-SSRs (Zhang et al, 2012).…”
Section: Ssr Polymorphismcontrasting
confidence: 76%
“…The same study also unraveled a sampling bias for the used diversity array technology markers. Würschum et al (2013) compared SNP and SSR markers in wheat and found only low congruency among the genetic relatedness matrices estimated with the two marker types. As genetic relatedness is one of the major forces exploited in genomic selection, substantial differences are expected for the prediction models trained with SNP or SSR markers in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature only relatively high averages of short range LD values have been reported, for example in crop species such as wheat (Würschum et al 2013)and maize (Yan et al 2009), where average initial LD of r 2 = 0.32 and r 2 = 0.24 respectively were observed, in (Wang et al 2013) even averages of r 2 = 0.5 are observed. We observed a lower average r 2 for short range LD in our data (r 2 is between 0.19 and 0.22).…”
Section: Short Range Ld In the Variety Panelmentioning
confidence: 99%
“…In many studies a restriction on the MAF is applied, where a 5% cutoff is most commonly used (Zhao et al 2011;Delourme et al 2013;Esteras et al 2013;Wang et al 2013;Würschum et al 2013;Adetunji et al 2014;Li et al 2014). In some cases a 10% (Hyten et al 2007;Comadran et al 2011) or even a 20% cut-off (Branca et al 2011) is used.…”
Section: Effect Of Maf On Ld-decaymentioning
confidence: 99%